THE SPIRITUAL AND RELIGIOUS PRACTICE OF â€œJEEDOâ€AMONG ELDERLY WOMEN IN BAUCHI EMIRATE OF NORTH EASTERN NIGERIA - Yakubu, Abubakar; Namadi, Mohammed Mustapha (Journal of Techno-Social, 2018)
AbstractÂ Population ageing has been identified as one of the most potential crises across the globe that requires urgent attention.Â  One of the most crucial issues related to this development is the issue of the quality life of older adults. The study describes a spiritual practice among elderly women that has stood the test of time, referred to as Jeedo. The study uses participatory research methods and data was analyzed using thematic analysis. Findings revealed that, the Jeedo has been practiced for over two hundred as system of spiritual devotion and getting closer to Allah (SWT) in preparation for death. The practice has eventually expanded into a formidable network of elderly women who are devoted to the service of the society and mutual help within them. It is recommended that, with empowerment sensitization and change of attitude the Jeedo can be modelled across the eastern Nigeria and beyond.Â Â Â Â Â Â Â Â Â